2021
DOI: 10.1093/toxres/tfab118
|View full text |Cite
|
Sign up to set email alerts
|

The chemoprevention of spirulina platensis and garlic against diethylnitrosamine induced liver cancer in rats via amelioration of inflammatory cytokines expression and oxidative stress

Abstract: Natural antioxidant products play a vital role in the treatment and prevention of cancer disease because they have no side effects. This study aimed to compare the chemoprotective effect of Spirulina platensis (SP) and garlic against hepatocellular carcinoma (HCC) in rats. This study was being done by using 60 male Wistar rats and divided into four groups. Group (I): normal group. Group (II): HCC group induced by injection of a single dose of DEN (200 mg/kg/I.P) and after 14 days injected CCl4 (1 mg/kg/I.P) 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
3
6
0
Order By: Relevance
“…Our results revealed that SOR, NSP, or combined NSP /SOR downregulated the inflammatory cytokines with marked improvement in HCC-treated rats with a combined NSP/SOR; these data were in line with [ 49 ], where Arthrospira platensis reduced the hepatic expression of TNF-, IL-6, iNOS, and TGF-1.…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that SOR, NSP, or combined NSP /SOR downregulated the inflammatory cytokines with marked improvement in HCC-treated rats with a combined NSP/SOR; these data were in line with [ 49 ], where Arthrospira platensis reduced the hepatic expression of TNF-, IL-6, iNOS, and TGF-1.…”
Section: Discussionsupporting
confidence: 90%
“…The ERK pathway is one of the major oncogenic signals in human cancers because its activation leads to an increase in proliferation, invasion, and metastasis [49][50][51]. The ERK pathway is often hyperactivated in tumors [52] and acts as an inducer of cell migration and invasion through a Snail-mediated mechanism [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…We show for the rst time that LPAR5 can regulate Snail expression through the ERK pathway and mediate IR-induced EMT. The highly expressed LPAR5 upregulates the expression of Snail through the ERK pathway, thereby affecting the expression of MMP1 and MMP9.The ERK pathway is one of the major oncogenic signals in human cancers because its activation leads to an increase in proliferation, invasion, and metastasis [49][50][51]. The ERK pathway is often hyperactivated in tumors [52], acts as an inducer of cell migration and invasion through a Snail-mediated mechanism [53][54][55][56].MMPs can degrade various protein components in the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%